Utilization of Webcam Cameras as X-Ray Image Capture (kV Settings and Shutter Sensors) - Ni Made Wagiswari Dwara; Muhammad Ridha Mak’ruf; Tri Bowo Indrato (Indonesian Journal of Electronics, Electromedical Engineering, and Medical Informatics, 2023)
The result of x-ray imagery is generally in the form of film sheets. To obtain an image, the film must pass through the process of processing with chemicals. Departing from these problems, efforts were made to develop digital x-ray detectors using much cheaper devices. By using voltage variations and also sensors that aim to find out the difference in the quality of the resulting image. The contribution of this study is that the system can display negative image results from webcam camera captures that have previously passed the image processing process with the Matrix Laboratory (MATLAB) Application. The measurement ranges used are 60, 65, and 70 kV. with a set mA of 25mA, a duration of irradiation of 1 second, and a moderate intensity of illumination light. From the measurement results, it shows that the X-ray Image Capture Tool can be compared with the image results from the Philip brand DR with the MSE value obtained, which is 34.8775 with parameters Phototransistor BPT1331, 70kV, and 25mA. And the lowest MSE value is 61.7615 with parameters LDR, 66kV, 25mA. The results of this study indicate that the tool can be used to capture X-rays.